Positive active material, positive electrode, and rechargeable lithium batteries
Patent Information
- Application Number
- KR1020230101768
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2043-08-03
Smart Images

Figure 112023085832892-PAT00001_ABST
Abstract
Description
Technology Field
[0001] This invention relates to a positive electrode active material and a positive electrode and a lithium secondary battery containing the same. Background Technology
[0002] Lithium-ion batteries, which offer high energy density and portability, are primarily used as the power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research is being conducted to utilize high-energy-density lithium-ion batteries as power sources for driving or energy storage in hybrid and electric vehicles.
[0003] Various cathode active materials are being considered to realize lithium secondary batteries suitable for these applications. Among them, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are primarily used as cathode active materials. However, while the demand for large-capacity or high-energy-density lithium secondary batteries has recently surged, the supply of cathode active materials containing the rare metal cobalt is expected to be woefully insufficient. In other words, because cobalt is expensive and its remaining reserves are limited, there is a need to develop cathode active materials that exclude cobalt or reduce its content. The problem to be solved
[0004] The present invention provides a cathode active material comprising a lithium nickel-manganese-based composite oxide, which innovatively reduces the cost of the cathode material while securing high capacity and high energy density characteristics, and improves high voltage performance by suppressing side reactions with the electrolyte at high voltage, as well as a cathode comprising the same and a lithium secondary battery. means of solving the problem
[0005] In one embodiment, a positive electrode active material is provided comprising: a first positive electrode active material in the form of a secondary particle formed by aggregating a plurality of primary particles, containing a lithium nickel-manganese composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of the total metal excluding lithium; a second positive electrode active material in the form of a single particle, containing a lithium nickel-manganese composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of the total metal excluding lithium; and a third positive electrode active material in the form of a particle containing a lithium manganese oxide.
[0006] In another embodiment, the positive electrode comprises a positive current collector and a positive active material layer located on the positive current collector, wherein the positive active material layer comprises the aforementioned positive active material.
[0007] In another embodiment, a lithium secondary battery comprising the anode, cathode, and electrolyte is provided. Effects of the invention
[0008] The cathode active material according to one embodiment maximizes capacity while minimizing production costs, ensures long lifespan characteristics, and suppresses adverse reactions with the electrolyte at high voltage. A lithium secondary battery applying the above cathode active material can exhibit high initial charge / discharge capacity and efficiency even under high-voltage operating conditions and can achieve long lifespan characteristics. Brief explanation of the drawing
[0009] FIG. 1 is a cross-sectional view schematically showing a lithium secondary battery according to one embodiment. Figure 2 is a scanning electron microscope (SEM) image of the first positive electrode active material of Example 1. Figure 3 is an SEM image of the second positive active material of Example 1. Figures 4 and 5 are SEM images of the third positive electrode active material of Example 1. Specific details for implementing the invention
[0010] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.
[0011] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.
[0012] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.
[0013] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0014] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.
[0015] In addition, the term “layer” here includes not only shapes formed on the entire surface when viewed in a plan view, but also shapes formed on some surfaces.
[0016] The average particle size can be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with transmission electron microscope images or scanning electron microscope images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering and performing data analysis to count the number of particles for each particle size range, and then calculating from this. Unless otherwise defined, the average particle size may refer to the diameter (D50) of a particle whose cumulative volume is 50% of the particle size distribution. Additionally, unless otherwise defined, the average particle size may be obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles from a scanning electron microscope image to obtain a particle size distribution, and taking the diameter (D50) of the particle whose cumulative volume is 50% of the particle size distribution as the average particle size.
[0017] Here, “or” is not interpreted in an exclusive sense; for example, “A or B” is interpreted to include A, B, A+B, etc.
[0018] The term “metal” is interpreted as a concept that includes ordinary metals, transition metals, and metalloids (semimetals).
[0019] positive electrode active material
[0020] In one embodiment, a positive electrode active material is provided comprising: a first positive electrode active material in the form of a secondary particle formed by aggregating a plurality of primary particles, containing a lithium nickel-manganese composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of the total metal excluding lithium; a second positive electrode active material in the form of a single particle, containing a lithium nickel-manganese composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of the total metal excluding lithium; and a third positive electrode active material in the form of a particle containing a lithium manganese oxide.
[0021] With the recent surge in the price of the rare metal cobalt, there is a growing demand for the development of cathode active materials that exclude or reduce the cobalt content. Among these, cathode active materials with olivine-based crystal structures, such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium iron manganese phosphate (LMFP), face limitations in achieving high capacity due to the low available lithium capacity within their structures. Layered nickel-manganese cathode active materials are suitable for high-capacity batteries due to their excellent capacity and efficiency characteristics resulting from high available lithium capacity; however, the removal of cobalt, which plays a key role in the layered structure, leads to reduced structural stability, increased resistance, and difficulties in ensuring long lifespan characteristics. Furthermore, the exclusion of cobalt accelerates side reactions between the cathode active material and the electrolyte under high voltage and high temperature conditions, resulting in increased gas generation and degraded lifespan characteristics.
[0022] In one embodiment, a first positive active material in the form of secondary particles and a second positive active material in the form of single particles are mixed, and a third positive active material containing a lithium manganese-based oxide, which is a low-cost material, is mixed therein, thereby proposing a positive active material that achieves high capacity and high energy density, while also achieving long lifespan characteristics and improved high voltage performance.
[0023] Average particle size (D) of secondary particles of the first positive active material 50 ) is the average particle size (D) of the single particles of the second positive active material. 50 It can be larger than ). In this case, the first positive electrode active material can be expressed as an opposite or an allotrope, and the second positive electrode active material can be expressed as a subatomic particle or a subatomic particle. The average particle size (D) of the secondary particles of the first positive electrode active material. 50 ) is the average particle size (D) of the third positive electrode active material. 50 It can be larger than ). Average particle size of the third cathode active material (D 50 ) is the average particle size (D) of the single particles of the second positive active material. 50It can be equal to or greater than ). As a lithium nickel-manganese oxide, capacity and energy density can be maximized and high voltage characteristics improved by appropriately mixing secondary particle-shaped coarse particles and single particle-shaped subarctobers and additionally mixing lithium manganese oxide.
[0024] Here, the average particle size is determined by obtaining a particle size distribution by randomly measuring the size (diameter or length of the major axis) of about 20 particles from scanning electron microscope images of the cathode active materials, and the diameter (D) of the particle with a cumulative volume of 50 volume% in the said particle size distribution. 50 It may be that ) was taken as the average particle size.
[0025] Average particle size (D) of the secondary particles of the first positive active material 50 ) may be, for example, 10 µm to 20 µm, 10 µm to 18 µm, or 12 µm to 16 µm. The average particle size (D) of the single particles of the second positive active material. 50 ) may be, for example, 0.5 μm to 8 μm, 1 μm to 7 μm, 1.5 μm to 6 μm, or 2 μm to 5 μm. The average particle size (D) of the particles of the third positive active material. 50 The average particle size of each cathode active material can be 5 μm to 12 μm, for example, 6 μm to 11 μm, or 7 μm to 10 μm. When the average particle size of each cathode active material satisfies the above range, high capacity can be achieved and energy density can be maximized.
[0026] With respect to the total of 100% by weight of the first positive active material, the second positive active material, and the third positive active material, the first positive active material may be included in an amount of 60% to 90% by weight, the second positive active material may be included in an amount of 5% to 35% by weight, and the third positive active material may be included in an amount of 5% to 35% by weight. As a specific example, the first positive active material may be included in an amount of 60% to 85% by weight, the second positive active material may be included in an amount of 10% to 25% by weight, and the third positive active material may be included in an amount of 5% to 20% by weight. When the mixing ratio of each positive active material satisfies the above range, the energy density can be further increased while increasing the capacity.
[0027] The lithium nickel-manganese composite oxide of the first cathode active material and the lithium nickel-manganese composite oxide of the second cathode active material may be identical or different from each other. In each lithium nickel-manganese composite oxide, the nickel content satisfies 60 mol% or more relative to 100 mol% of the total metal excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, high capacity can be achieved and structural stability can be increased even if the cobalt content is reduced.
[0028] The manganese content may be, for example, 10 mol% to 40 mol% with respect to 100 mol% of the total metal excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. When the manganese content satisfies the above range, the cathode active material can achieve high capacity while improving structural stability.
[0029] In each of the first and second positive active materials, the lithium nickel-manganese composite oxide may be a lithium nickel-manganese-aluminum composite oxide containing aluminum in addition to nickel and manganese. When aluminum is included in the composite oxide, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The aluminum content per 100 mol% of the lithium nickel-manganese-aluminum composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, and for example, may be 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the aluminum content satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, the problem of structural collapse due to charging and discharging can be suppressed, and long-life characteristics of the positive active material can be realized.
[0030] The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material can each be independently represented by the following chemical formula 1.
[0031] [Chemical Formula 1]
[0032] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O2-b1 X b1
[0033] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1 and M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
[0034] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. Additionally, Chemical Formula 1 may contain aluminum, in which case it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29, for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 <z1≤0.03, 및 0≤w1≤0.29를 만족할 수 있다.
[0035] In Chemical Formula 1, for example, 0.6≤x1≤0.79, 0.6≤x1≤0.78, 0.6≤x1≤0.75, 0.65≤x1≤0.8, or 0.7≤x1≤0.79, 0.1≤y1≤0.35, 0.1≤y1≤0.30, 0.1≤y1≤0.29, 0.15≤y1≤0.39, or 0.2≤y1≤0.3, and 0.01≤z1≤0.025, 0.01 <z1≤0.02, 또는 0.01<z1≤0.019일 수 있고, 0≤w1≤0.28, 0≤w1≤0.27, 0≤w1≤0.26, 0≤w1≤0.25, 0≤w1≤0.24, 0≤w1≤0.23, 0≤w1≤0.22, 0≤w1≤0.21, 0≤w1≤0.2, 0≤w1≤0.15, 0≤w1≤0.1, 또는 0≤w1≤0.09 등일 수 있다.
[0036] The above lithium nickel-manganese composite oxide may be a cobalt-free compound that does not contain cobalt or contains a very small amount. That is, the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material may each independently have a cobalt content of 0 mol% to 0.01 mol% relative to 100 mol% of the total metal excluding lithium.
[0037] First positive active material
[0038] According to one embodiment, the concentration of aluminum within the secondary particles of the first cathode active material, excluding the coating layer, may be uniform. That is, it means that the aluminum concentration within the particles is not uniform, with no concentration gradient from the center to the surface, nor is the aluminum concentration higher or lower outside than inside the particles, and that the aluminum is evenly dispersed within the particles. This structure is obtained by synthesizing a composite oxide using a nickel-manganese-aluminum hydroxide as a precursor, by using aluminum raw materials during the preparation of the precursor, without additionally doping aluminum during the cathode active material synthesis process. In other words, the aluminum content within the primary particles may be the same or similar regardless of the position of the primary particles. If the primary particles are selected at an arbitrary position in the cross-section of the secondary particles and the aluminum content is measured inside rather than at the interface of the primary particles, the aluminum content can be described as the same, similar, or uniform regardless of the position of the primary particles, that is, whether the primary particles are close to the center or the surface of the secondary particles. In such a structure, a stable layered structure can be maintained even if cobalt is absent or present in minute quantities, and since no aluminum byproducts or aluminum aggregates are generated, the capacity, efficiency, and lifespan characteristics of the cathode active material can be simultaneously improved.
[0039] According to one embodiment, the first positive active material may further include a coating layer containing aluminum and zirconium located on the surface of the secondary particle. By including an aluminum-zirconium-rich layer on the surface of the first positive active material, side reactions with the electrolyte at high voltage can be effectively suppressed, thereby improving capacity and lifespan characteristics at high voltage.
[0040] With respect to 100 mol% of the total metal excluding lithium in the first positive active material, the aluminum content of the coating layer may be 0.1 mol% to 2 mol% and the zirconium content of the coating layer may be 0.05 mol% to 1 mol%. The aluminum content of the coating layer in the first positive active material may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. The content of aluminum or zirconium, etc. in the coating layer can be measured, for example, through SEM-EDS analysis of the surface or cross-section of the positive active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer of uniform and thin thickness, the resistance of the positive active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery at high voltage.
[0041] The zirconium content of the coating layer in the first positive electrode active material may be, for example, 0.1 mol% to 1 mol%, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, or 0.1 mol% to 0.6 mol%. When the zirconium content satisfies the above range, the positive electrode active material forms a good coating layer without reducing capacity or increasing resistance, effectively suppressing adverse reactions with the electrolyte, and further improving capacity characteristics and lifespan characteristics under high voltage driving conditions.
[0042] The coating layer of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium, and in this case, the content of yttrium may be 0.1 mol% to 1 mol% with respect to 100 mol% of the total metal excluding lithium of the first positive electrode active material.
[0043] The coating layer of the first positive active material may be in the form of a film that continuously covers the surface of the secondary particle, or, for example, in the form of a shell that covers the entire surface of the secondary particle. This is distinguished from a structure in which only a part of the surface of the secondary particle is partially coated. According to one embodiment, the coating layer can be formed to completely cover the surface of the secondary particle while having a very thin and uniform thickness. Accordingly, the positive active material does not experience an increase in resistance or a decrease in capacity, its structural stability is improved, side reactions with the electrolyte are effectively suppressed, the amount of gas generated under high voltage and high temperature conditions is reduced, and long life characteristics can be realized.
[0044] The thickness of the coating layer of the first positive electrode active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the structural stability of the positive electrode active material can be improved and side reactions with the electrolyte can be effectively suppressed without increasing resistance or decreasing capacity due to the coating. The thickness of the coating layer may be measured, for example, through TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer may be measured through a TEM-EDS line profile.
[0045] The coating layer of the first positive active material is characterized by being thin, with a thickness of tens to hundreds of nanometers, yet having a uniform thickness. For example, the variation in coating layer thickness within a single positive active material particle may be 20% or less, 18% or less, or 15% or less. Here, the variation in coating layer thickness refers to the thickness of the coating layer within a single positive active material particle. The variation in coating layer thickness may mean, for example, measuring the thickness at about 10 points in an electron microscope image of a cross-section of a single positive active material particle, calculating the arithmetic mean, dividing the absolute value of the difference between a single data point and the arithmetic mean value by the arithmetic mean value, and multiplying by 100. When the variation or standard deviation of the coating layer thickness satisfies the above range, it means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive active material particle. Accordingly, the structural stability of the positive active material is improved, side reactions with the electrolyte are effectively suppressed, and the increase in resistance or decrease in capacity caused by the coating can be minimized.
[0046] Meanwhile, aluminum may diffuse into the secondary particles during the coating layer formation process. Accordingly, the cathode active material according to one embodiment may further include a grain boundary coating portion containing aluminum located on the surface of the primary particles inside the secondary particles. The term "inside the secondary particles" may refer to the entire interior excluding the surface of the secondary particles, or it may refer to an area extending from the surface of the secondary particles toward the center of the secondary particles up to approximately 60% of the radius. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the secondary particles and refers to a coating portion formed on the surface of the primary particles located inside the secondary particles. The presence of the grain boundary coating portion can be confirmed through SEM-EDS analysis of the cross-section of the cathode active material. By forming the aluminum grain boundary coating portion, the cathode active material can be structurally further stabilized and its lifespan characteristics improved.
[0047] The aluminum content within the grain boundary coating portion is not particularly limited, and for example, the aluminum content within the grain boundary coating portion may be less than the aluminum content within the coating layer.
[0048] Meanwhile, the aluminum content of the coating layer of the first positive active material may be greater than the aluminum content of the coating layer of the second positive active material described later. For example, the aluminum content of the coating layer of the first positive active material and the aluminum content of the coating layer of the second positive active material may be in a molar ratio of 5:1 to 2:1, or 4:1 to 2:1. In this case, the aluminum in the coating layer of the first positive active material and the second positive active material does not act as a resistor, and can maximize capacity and lifespan characteristics at high voltage while improving the structural stability of each.
[0049] Second positive active material
[0050] The single particle of the second positive active material means that it exists alone without grain boundaries within the particle and consists of a single particle, and may mean a single particle, monolith structure, monolithic structure, or non-aggregated particle existing as an independent phase in terms of morphology where the particles are not aggregated together, and as an example, it may be a single crystal.
[0051] The second positive active material may further include a coating layer containing aluminum located on the surface of the single particle. In this case, the initial discharge capacity and lifespan characteristics at high voltage may be improved.
[0052] The aluminum content in the coating layer of the second positive electrode active material may be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the second positive electrode active material, and for example, may be 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This refers only to the content of aluminum contained in the coating layer, separate from the aluminum contained within the single particle. The aluminum content in the coating layer can be measured, for example, through SEM-EDS analysis of the surface or cross-section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer of uniform and thin thickness, the resistance of the positive electrode active material does not increase, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery under high voltage and high temperature conditions. For example, if the aluminum content of the coating layer is excessive, a uniform coating layer may not be formed or resistance may increase, which may degrade charge / discharge efficiency and lifespan characteristics; conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, which may reduce the effect of suppressing adverse reactions with the electrolyte.
[0053] The coating layer of the second positive electrode active material may further contain yttrium, in which case side reactions between the positive electrode active material and the electrolyte at high voltage can be more effectively suppressed to improve lifespan characteristics. The yttrium content in the coating layer is characterized as being 0.1 mol% to 1 mol% with respect to 100 mol% of the total metal excluding lithium in the second positive electrode active material, and may be, for example, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. When the yttrium content satisfies the above range, a good coating layer is formed on the positive electrode active material without a decrease in capacity or an increase in resistance, which can effectively suppress side reactions with the electrolyte and effectively reduce the amount of gas generated under high voltage or high temperature conditions.
[0054] The coating layer of the second positive active material may be in the form of a film that continuously covers the surface of a single particle, or, for example, in the form of a shell that covers the entire surface of the single particle. This is distinguished from a structure in which only a part of the surface of the particle is partially coated. According to one embodiment, the coating layer can be formed to completely cover the surface of the single particle while having a very thin and uniform thickness. Accordingly, the positive active material does not experience an increase in resistance or a decrease in capacity, its structural stability is improved, side reactions with the electrolyte can be effectively suppressed, and long life characteristics at high voltage can be realized.
[0055] The thickness of the coating layer of the second positive active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the structural stability of the positive active material can be improved and side reactions with the electrolyte can be effectively suppressed without increasing resistance or decreasing capacity due to the coating. The thickness of the coating layer may be measured, for example, through TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer may be measured through a TEM-EDS line profile.
[0056] The coating layer of the second positive active material is characterized by being thin, with a thickness of tens to hundreds of nanometers, yet having a uniform thickness. For example, the variation in coating layer thickness within a single positive active material particle may be 20% or less, 18% or less, or 15% or less. Here, the variation in coating layer thickness refers to the thickness of the coating layer within a single positive active material particle. The variation in coating layer thickness may mean, for example, measuring the thickness at about 10 points in an electron microscope image of a cross-section of a single positive active material particle, calculating the arithmetic mean, dividing the absolute value of the difference between a single data point and the arithmetic mean value by the arithmetic mean value, and multiplying by 100. When the variation or standard deviation of the coating layer thickness satisfies the above range, it means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive active material particle. Accordingly, the structural stability of the positive active material is improved, side reactions with the electrolyte are effectively suppressed, and the increase in resistance or decrease in capacity caused by the coating can be minimized.
[0057] Due to the characteristics of each element, aluminum can exist in the form of a continuous film in the coating layer of the second positive active material, and yttrium can exist in the form of an island.
[0058] In one embodiment, aluminum and yttrium may be mixed within a single coating layer, and in this case, aluminum may exist in the form of a continuous film and yttrium may exist in the form of an island, but are not limited to the form.
[0059] In another embodiment, aluminum and yttrium may each form separate layers. For example, the second positive active material may include a first coating layer containing aluminum located on the surface of a single particle, and a second coating layer containing yttrium located on the first coating layer. A first coating layer in the form of a thin film may be formed as aluminum first adheres to or is absorbed on the surface of the single particle, and a second coating layer may be formed as yttrium is coated thereon. Of course, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an aluminum-rich coating layer with aluminum as the main component, and the second coating layer may be an yttrium-rich coating layer with yttrium as the main component. Even in this case, yttrium may exist in an island form in the second coating layer, but is not particularly limited.
[0060] The thicknesses of the first coating layer and the second coating layer are not particularly limited, but the thickness of the first coating layer may be 10 nm to 200 nm, for example, 20 nm to 200 nm, 30 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer may be 20 nm to 300 nm, for example, 20 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the structural stability of the positive electrode active material is improved without increasing resistance or decreasing capacity due to the coating, and side reactions with the electrolyte are effectively suppressed, thereby improving lifespan characteristics at high voltage.
[0061] Third positive electrode active material
[0062] The third positive active material may be in the form of secondary particles formed by the aggregation of multiple primary particles.
[0063] The lithium manganese-based oxide of the third cathode active material may be, for example, a lithium manganese oxide with a spinel structure having LiMn2O4 as the basic composition. The lithium manganese-based oxide may further include, for example, aluminum, magnesium, yttrium, or a combination thereof in addition to manganese, and may not contain cobalt or may contain it in a very small amount.
[0064] The lithium manganese-based oxide of the third positive electrode active material can be represented, for example, by the following chemical formula 3.
[0065] [Chemical Formula 3]
[0066] Li a3 Mn x3 M 3 y3 O 4-b3 X b3
[0067] In Chemical Formula 3, 0.9≤a3≤1.8, 1.7≤x3≤2, 0≤y3≤0.3, 1.9≤x3+y3≤2.1, and 0≤b3≤0.1, and M 3 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
[0068] In Chemical Formula 3, 1.8≤x3≤2, 0≤y3≤0.2 or 1.9≤x3≤2, 0≤y3≤0.1 or 1.7≤x3<2, 0 <y3≤0.3일 수 있다.
[0069] Specifically, the lithium manganese-based oxide of the third positive electrode active material can be represented by the following chemical formula 4.
[0070] [Chemical Formula 4]
[0071] Li a4 Mn x4 Al y4 Mg z4 M 4 w4 O 4-b4 X b4
[0072] In Chemical Formula 4, 0.9≤a4≤1.8, 1.7≤x4<2.0, 0 <y4≤0.015, 0<z4≤0.010, 0≤w4<0.3, 1.9≤x4+y4+z4+w4≤2.1, 및 0≤b4≤0.1이고 M 4 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.
[0073] In the above lithium manganese-based oxide, Al may be included in an amount of 0 to 1.5 mol%, 0.01 mol% to 1.0 mol%, or 0.1 mol% to 0.8 mol% with respect to 100 mol% of the total metal excluding lithium, and Mg may be included in an amount of 0 to 1.0 mol%, 0.01 mol% to 0.9 mol%, or 0.1 mol% to 0.8 mol%.
[0074] The third positive electrode active material may further include a coating layer containing aluminum located on the surface of the particles. In this case, side reactions between the positive electrode active material and the electrolyte at high voltage can be effectively suppressed and lifespan characteristics can be improved. With respect to 100 mol% of the metal excluding lithium in the third positive electrode active material, the aluminum in the coating layer may be included in an amount of 0.01 mol% to 1 mol%, and for example, 0.05 mol% to 0.5 mol%.
[0075] In a positive electrode active material according to one embodiment, the content of cobalt may be, for example, 0.01 mol% or less, 0.005 mol% or less, 0.001 mol% or less with respect to 100 mol% of the total metal excluding lithium, and may be, for example, 0 mol% to 0.01 mol%, etc. The positive electrode active material according to one embodiment may be, for example, a cobalt-free positive electrode active material.
[0076] In addition, in one embodiment, the positive electrode active material may be characterized as not containing sodium. Generally, sodium ions may be used in the manufacturing process of the positive electrode active material; however, according to the manufacturing method described below, positive electrode active material particles with a stable structure and a coating layer of uniform thickness can be formed without using sodium ions.
[0077] Method for manufacturing positive electrode active material
[0078] In one embodiment, a method for manufacturing an anode active material is provided, comprising: (i) mixing a nickel-manganese-based composite hydroxide having a nickel content of 60 mol% or more relative to 100 mol% of the total metal and a lithium raw material and heat treating to prepare a first anode active material in the form of secondary particles formed by aggregating a plurality of primary particles; (ii) mixing a nickel-manganese-based composite hydroxide having a nickel content of 60 mol% or more relative to 100 mol% of the total metal and a lithium raw material and heat treating to prepare a second anode active material in the form of a single particle; (iii) preparing a third anode active material containing a lithium manganese-based oxide; and (iv) mixing the first anode active material, the second anode active material, and the third anode active material.
[0079] In the preparation process of the first and second cathode active materials, the nickel-manganese composite hydroxide may contain no cobalt or a very small amount of cobalt, and may be, for example, a cobalt-free nickel-manganese composite hydroxide, or, as an example, a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide may be manufactured by a general co-precipitation method.
[0080] In nickel-manganese composite hydroxides, the nickel content is 60 mol% or more relative to 100 mol% of the total metal, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, high capacity can be achieved and structural stability can be increased even if the cobalt content is reduced.
[0081] In the nickel-manganese composite hydroxide, the manganese content may be 10 mol% to 40 mol% with respect to 100 mol% of the total metal, and may be 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc.
[0082] In addition, when the nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more relative to 100 mol% of the total metal, and may be, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the manganese and aluminum content in the composite hydroxide each satisfy the above ranges, it is possible to achieve high capacity while increasing the structural stability of the cathode active material and lowering production costs to improve economic efficiency.
[0083] In nickel-manganese composite hydroxides, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less relative to 100 mol% of the total metal. Such nickel-manganese composite hydroxides are economical as they avoid the increase in unit cost caused by cobalt, and can be said to maximize capacity and improve structural stability.
[0084] Nickel-manganese complex hydroxides can be represented, for example, by the chemical formula 2 below.
[0085] [Chemical Formula 2]
[0086] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2
[0087] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1 and M2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr.
[0088] In the above chemical formula 2, for example, 6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0089] In the preparation process of the first cathode active material, aluminum is not additionally doped; instead, a nickel-manganese-aluminum composite hydroxide in which aluminum is evenly dispersed within the structure is used as a precursor by utilizing aluminum raw materials during precursor manufacturing. By using such a precursor, a cathode active material can be manufactured in which the layered structure is stably maintained even during repeated charge-discharge cycles, even without cobalt. Furthermore, since aluminum byproducts or aluminum aggregates are not formed, the capacity, efficiency, and lifespan characteristics of the cathode active material can be improved.
[0090] In the preparation process of the first cathode active material, the nickel-manganese-based composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, in a molar ratio of 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after mixing may be carried out in an oxygen atmosphere, for example, in a temperature range of 750 °C to 950 °C, or 780 °C to 900 °C, or 810 °C to 890 °C, and may be carried out for 2 to 20 hours, or 4 to 12 hours. Through the heat treatment, a lithium nickel-manganese-based composite oxide can be obtained. The obtained composite oxide may contain 60 mol% or more of nickel with respect to 100 mol% of the total metal, for example, in an amount of 60 mol% to 80 mol%, and may not contain cobalt or may contain a very small amount of 0.01 mol% or less.
[0091] A method for manufacturing a positive electrode active material according to one embodiment may further include a process of obtaining a lithium nickel-manganese composite oxide during the first positive electrode active material preparation process and then coating it. The lithium nickel-manganese composite oxide differs significantly from conventional nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxides or lithium nickel-cobalt-aluminum composite oxides, in terms of the residual lithium content on the particle surface and various surface characteristics; therefore, it is impossible to form a good coating layer in the form of a uniform film using conventional coating methods. In one embodiment, a method is proposed to improve high voltage characteristics by uniformly forming a coating layer with a very thin thickness on the surface of a lithium nickel-manganese composite oxide having a very small amount of cobalt and a nickel content of 60 mol% or more. For example, a coating layer according to one embodiment can be formed by adding and mixing an aluminum raw material into an aqueous solvent, adding and mixing the lithium nickel-manganese composite oxide, and then proceeding with drying and reheat treatment. This can be described as a wet coating method.
[0092] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, in which case it is advantageous to form a coating layer having a uniform thickness on the surface of lithium nickel-manganese-based composite oxide particles. The aluminum content in the aluminum raw material may be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the first cathode active material, and may be designed, for example, to be 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%.
[0093] A solution in which aluminum raw materials are mixed in an aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide is dropped into the aqueous solvent containing the aluminum raw materials and mixed, and the mixing process may be carried out for about 5 minutes to 80 minutes, or 5 minutes to 60 minutes, or 5 minutes to 40 minutes. The pH of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. Satisfying these conditions is advantageous for forming a coating layer of uniform thickness.
[0094] Reheat treatment can be understood as a process of forming a coating layer and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 to 20 hours, or 3 to 10 hours.
[0095] In order to coat not only aluminum but also zirconium, a zirconium raw material may be added to the product after the drying process and reheat treated. The zirconium raw material may be, for example, zirconium oxide, and may be added such that the zirconium content is 0.05 mol% to 1 mol% with respect to 100 mol% of metal excluding lithium in the first positive electrode active material.
[0096] In the process of preparing the second cathode active material, the nickel-manganese-based composite hydroxide and the lithium raw material can be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, in a molar ratio of 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after mixing can be carried out in an oxygen atmosphere, for example, in a temperature range of 750 °C to 950 °C, or 780 °C to 900 °C, or 810 °C to 890 °C, and can be carried out for 2 to 20 hours, or 4 to 12 hours. Through the heat treatment, a lithium nickel-manganese-based composite oxide can be obtained. The obtained composite oxide may contain 60 mol% or more of nickel relative to 100 mol% of the total metal, for example, in an amount of 60 mol% to 80 mol%, and may not contain cobalt or may contain a very small amount of 0.01 mol% or less. To obtain a single particle form, a grinding process may be further included after manufacturing the lithium nickel-manganese-based composite oxide.
[0097] In the process of preparing the second positive electrode active material, a process of coating the single particles after obtaining single particles containing a lithium nickel-manganese composite oxide by mixing a nickel-manganese composite hydroxide and a lithium raw material and heat-treating them may be further included. When coating aluminum onto the second positive electrode active material in the form of single particles, it is not possible to apply the existing coating method as is, but a good coating layer in the form of a uniform film can be formed by applying a wet coating method according to one example. That is, the second positive electrode active material can be manufactured by adding the obtained single-particle lithium nickel-manganese composite oxide to a solution in which an aluminum raw material is mixed in an aqueous solvent, mixing it, drying it, and then re-heat-treating it.
[0098] The contents regarding the aqueous solvent and the aluminum raw material are as described above. The aluminum content in the aluminum raw material can be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the second cathode active material, and, for example, can be designed to be 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%.
[0099] Al and Y may be coated by adding yttrium raw materials together when adding aluminum raw materials to an aqueous solvent. The yttrium raw materials may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The yttrium content in the yttrium raw materials may be designed to be 0.1 mol% to 1 mol% with respect to 100 mol% of the total metal excluding lithium in the second cathode active material, and may be designed, for example, to be 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. By designing the content of the coating raw materials to each of the above ranges, it is possible to form a coating layer with a uniform thickness and a thin thickness of tens to hundreds of nanometers, and to reduce the amount of gas generated in the lithium secondary battery under high voltage operating conditions and improve high capacity and long life characteristics.
[0100] The solution obtained by mixing the above aluminum raw material and optionally the yttrium raw material in an aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide is dropped into the aqueous solvent containing the mixture of aluminum raw material and yttrium raw material and mixed, and the mixing may be carried out for about 5 minutes to 80 minutes, or 5 minutes to 60 minutes, or 5 minutes to 40 minutes. The pH of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. Satisfying these conditions is advantageous for forming a coating layer of uniform thickness.
[0101] Drying after the above mixing process can be understood as a process of removing the solvent and may be carried out, for example, at 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C. Reheat treatment can be understood as a process of forming a coating layer and may be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 to 20 hours, or 3 to 10 hours. Additionally, the reheat treatment temperature may be lower than the preceding heat treatment temperature, and the reheat treatment time may be equal to or shorter than the preceding heat treatment time. A desired coating layer can be obtained by performing reheat treatment under these conditions.
[0102] The first positive active material, the second positive active material, and the third positive active material can be mixed such that, with respect to the total of 100 weight%, the first positive active material is included in an amount of 60 weight% to 90 weight%, the second positive active material is included in an amount of 5 weight% to 35 weight%, and the third positive active material is included in an amount of 5 weight% to 35 weight%. As a specific example, the first positive active material can be included in an amount of 60 weight% to 85 weight%, the second positive active material in an amount of 10 weight% to 25 weight%, and the third positive active material in an amount of 5 weight% to 20 weight%. When each positive active material is mixed in the above ratios, the energy density can be maximized while increasing the capacity.
[0103] anode
[0104] In one embodiment, a positive electrode is provided that includes a positive current collector and a positive active material layer located on the positive current collector, wherein the positive active material layer comprises the aforementioned positive active material. The positive active material layer may further include other types of positive active materials in addition to the aforementioned positive active material. Additionally, the positive active material layer may optionally further include a binder, a conductive material, or a combination thereof.
[0105] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm² 2 to 40 mg / cm² 2 It could be, for example, 10 mg / cm² 2 to 30 mg / cm² 2 or 10 mg / cm² 2 to 20 mg / cm² 2In addition, the density of the positive active material layer in the rolled final positive may be 3.5 g / cc to 3.7 g / cc, for example, 3.5 g / cc to 3.6 g / cc or 3.5 g / cc to 3.58 g / cc. When applying the positive active material according to one embodiment, it is advantageous to achieve such loading levels and positive densities, and a positive electrode satisfying the loading levels and positive densities within the above range is suitable for realizing a high-capacity, high-energy-density lithium secondary battery.
[0106] bookbinder
[0107] The binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples of binders include, but are not limited to, polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0108] Challenge
[0109] A conductive material is used to impart conductivity to an electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0110] The content of the binder and the conductive material may be 0.5% to 5% by weight, or 0.5% to 3% by weight, respectively, with respect to 100% by weight of the positive active material layer.
[0111] Al can be used as the positive current collector, but is not limited to it.
[0112] lithium secondary battery
[0113] In one embodiment, a lithium secondary battery comprising the aforementioned positive electrode, negative electrode, and electrolyte is provided.
[0114] Lithium secondary batteries can be classified into cylindrical, prismatic, pouch, coin, etc., depending on their shape. FIG. 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Referring to FIG. 1, the lithium secondary battery (100) may include an electrode assembly (40) having a separator (30) interposed between a positive electrode (10) and a negative electrode (20), and a case (50) in which the electrode assembly (40) is housed. The positive electrode (10), the negative electrode (20), and the separator (30) may be impregnated with an electrolyte (not shown).
[0115] A lithium secondary battery according to one embodiment may be capable of being charged at a high voltage or suitable for being operated at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.3 V to 4.6 V, or 4.40 V to 4.55 V. By applying a positive electrode active material according to one embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage and can achieve high capacity and long life characteristics.
[0116] cathode
[0117] The cathode may include a current collector and a layer of cathode active material located on the current collector, and may further include a binder, a conductive material, or a combination thereof.
[0118] cathode active material
[0119] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0120] A material capable of reversibly intercalating / deintercalating the above lithium ions may be a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0121] As the above lithium metal alloy, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0122] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used. The above Si-based negative electrode active material may include silicon, silicon-carbon composites, and SiOx(0 <x<2), Si-Q 합금(상기 Q는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소(Si를 제외함), 15족 원소, 16족 원소, 전이금속, 희토류 원소 및 이들의 조합에서 선택되는 원소이며, 예컨대 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, 및 이들의 조합에서 선택됨), 또는 이들의 조합일 수 있다. 상기 Sn계 음극 활물질로는 Sn, SnO2, Sn 합금 또는 이들의 조합일 수 있다.
[0123] The above silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D) of the silicon-carbon composite particles 50 The thickness may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include a secondary particle (core) assembled from silicon primary particles and an amorphous carbon coating layer (shell) located on the surface of the secondary particle. The amorphous carbon may also be located between the silicon primary particles, so that, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0124] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. Examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0125] When the silicon-carbon composite comprises silicon and amorphous carbon, the silicon content may be 10% to 50% by weight with respect to 100% by weight of the silicon-carbon composite, and the amorphous carbon content may be 50% to 90% by weight. Additionally, when the composite comprises silicon, amorphous carbon, and crystalline carbon, the silicon content may be 10% to 50% by weight with respect to 100% by weight of the silicon-carbon composite, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight.
[0126] In addition, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D) of the silicon particles (primary particles) 50 ) can be 10 nm to 1 µm, or 10 nm to 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon is SiO x (0 <x<2)로 표시될 수 있다. 이때, 산화 정도를 나타내는 Si:O의 원자 함량 비율은 99:1 내지 33:67일 수 있다. 본 명세서에서, 별도의 정의가 없는 한, 평균 입경(D 50 ) refers to the diameter of the particle with a cumulative volume of 50 volume% in the particle size distribution.
[0127] The above Si-based negative electrode active material or Sn-based negative electrode active material may be used in combination with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be 1:99 to 90:10 by weight.
[0128] bookbinder
[0129] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof may be used.
[0130] Examples of non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide imide, polyimide, or combinations thereof.
[0131] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0132] When a water-based binder is used as the cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal.
[0133] The dry binder is a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0134] Challenge
[0135] A conductive material is used to impart conductivity to an electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjenblack, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0136] The content of the negative electrode active material may be 95% to 99.5% by weight with respect to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight with respect to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.
[0137] The whole house
[0138] The negative current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and may be in the form of a foil, sheet, or foam. The thickness of the negative current collector may be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0139] electrolytes
[0140] The electrolyte for a lithium secondary battery may be, for example, an electrolyte solution, which may include a non-aqueous organic solvent and a lithium salt.
[0141] Non-aqueous organic solvents serve as a medium through which ions involved in the electrochemical reaction of a cell can move. Non-aqueous organic solvents may be carbonate-based, ester-based, ether-based, ketone-based, or alcohol-based solvents, aprotic solvents, or a combination thereof.
[0142] Carbonate-based solvents that may be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester-based solvents that may be used include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methylpropionate, ethylpropionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. As ether-based solvents, dibutyl ether, tetraglame, diglame, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. may be used. Additionally, as ketone-based solvents, cyclohexanone, etc. may be used. As alcohol-based solvents, ethyl alcohol, isopropyl alcohol, etc. may be used, and as aprotic solvents, nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms and may include a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane, 1,4-dioxolane; sulfolanes, etc. may be used.
[0143] Non-aqueous organic solvents can be used alone or in a mixture of two or more types, and when two or more types are mixed, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.
[0144] When using a carbonate-based solvent, a mixture of cyclic carbonates and chain carbonates can be used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of 1:1 to 1:9.
[0145] The non-aqueous organic solvent may further include an aromatic hydrocarbon-based organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon-based organic solvent may be mixed and used in a volume ratio of 1:1 to 30:1.
[0146] The electrolyte may further include vinyl ethyl carbonate, vinylene carbonate, or ethylene carbonate-based compounds to improve battery life.
[0147] Representative examples of the above ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0148] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions within the battery, enabling the basic operation of rechargeable lithium batteries and facilitating the movement of lithium ions between the anode and cathode. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 It may include one or more selected from SO2)(x and y are integers from 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluorobis(oxalate)phosphate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).
[0149] It is preferable to use a lithium salt concentration within the range of 0.1M to 2.0M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate ionic conductivity and viscosity, so it can exhibit excellent performance and lithium ions can move effectively.
[0150] separator
[0151] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers thereof may be used, and of course, mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators may be used.
[0152] The above separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0153] The porous substrate may be a polymer membrane formed from any one of the following: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene oxide; cyclic olefin copolymer; polyphenylene sulfide; polyethylene naphthalate; glass fiber; Teflon; and polytetrafluoroethylene, or a copolymer or mixture of two or more of these.
[0154] The porous substrate may have a thickness of about 1 μm to 40 μm, and may have a thickness of, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0155] The above organic material may include a (meth)acrylic copolymer comprising a first structural unit derived from (meth)acrylamide, and a second structural unit comprising at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamideidosulfonic acid or its salt.
[0156] The above inorganic materials are Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, It may include inorganic particles selected from SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D) of the inorganic particles 50 ) can be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0157] The above organic and inorganic materials may exist mixed in a single coating layer, or may exist in a stacked form with a coating layer containing organic materials and a coating layer containing inorganic materials.
[0158] The thickness of the coating layer may be 0.5 μm to 20 μm, for example, 1 μm to 10 μm, or 1 μm to 5 μm.
[0159] Examples and comparative examples of the present invention are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0160] Example 1
[0161] 1. Preparation of positive electrode active material
[0162] (1) Preparation of the first positive active material
[0163] Ni 0.75 Mn 0.23 Al0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and subjected to a first heat treatment at 850 °C for 8 hours in an oxygen atmosphere to obtain a composition of Li1.05Ni 0.75 Mn 0.23 Al 0.02 O2 and average particle size (D 50 A first composite oxide in the form of secondary particles with a thickness of approximately 14 μm was prepared.
[0164] Aluminum sulfate was added to a distilled water solvent, followed by the addition of the first complex oxide, and the mixture was mixed for approximately 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% relative to 100 mol% of the total metals excluding lithium in the final first cathode active material. After removing the solvent from the mixed solution and drying at 190°C, zirconium oxide was added to the product, and a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to produce the first cathode active material. The zirconium content in the zirconium oxide was designed to be 0.2 mol% relative to 100 mol% of the total metals excluding lithium in the final first cathode active material. Figure 2 is an SEM image of the prepared first cathode active material. The average particle size (D) of the secondary particles of the prepared first cathode active material 50 ) is approximately 14㎛.
[0165] (2) Preparation of the second positive active material
[0166] Ni 0.75 Mn 0.25 (OH)2, LiOH, and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated at 850 °C for 8 hours in an oxygen atmosphere to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and average particle size (D 50 A second complex oxide in the form of a single particle with a particle size of approximately 3 μm was prepared.
[0167] Aluminum sulfate and yttrium nitrate were mixed in a distilled water solvent, and then the second composite oxide was added and mixed for approximately 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 0.4 mol% relative to 100 wt% of the total metals excluding lithium in the final second cathode active material, and the yttrium content in the yttrium nitrate was designed to be 0.1 mol%, and the mixture was prepared accordingly. After removing the solvent from the mixed solution and drying at 190°C, the second cathode active material was prepared by heat treatment at 825°C for 8 hours in an oxygen atmosphere. Figure 3 is an SEM image of the prepared second cathode active material. The average particle size (D) of the single particles of the prepared second cathode active material 50 ) is approximately 3.5㎛.
[0168] (3) Preparation of the third positive active material
[0169] Mn3O4, Li2CO3, Al2O3, and MgCO3 were mixed in a molar ratio of 1:1:0.005:0.005 and heat-treated at 700 °C for 8 hours in an oxygen atmosphere to obtain a composition of LiMn 1.99 Mg 0.005 Al 0.005 O4 and average particle size (D 50 A second composite oxide in the form of a single particle with a particle size of approximately 7.5 μm was prepared.
[0170] Figures 4 and 5 are SEM images of the third positive electrode active material.
[0171] (4) Preparation of the final positive active material
[0172] A final positive active material was prepared by mixing 70 wt% of a first positive active material, 20 wt% of a second positive active material, and 10 wt% of a third positive active material.
[0173] 2. Manufacture of the anode
[0174] A cathode active material layer slurry was prepared by mixing 98.5 wt% of the manufactured cathode active material, 1.0 wt% of a polyvinylidene fluoride binder, and 0.5 wt% of a carbon nanotube conductive material, and the slurry was coated onto an aluminum foil current collector, dried, and rolled to produce a cathode. The density of the final rolled cathode was approximately 3.52 g / cc.
[0175] 3. Manufacture of lithium secondary batteries
[0176] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% of graphite negative electrode active material, 1.5 wt% of carboxymethyl cellulose, and 1 wt% of styrene butadiene rubber in a water solvent. A negative electrode was prepared by coating the negative electrode active material layer slurry onto a copper foil current collector, drying, and rolling.
[0177] A lithium secondary battery (coin cell) was manufactured by a conventional method using a polytetrafluoroethylene separator and an electrolyte in which 1M LiPF6 was dissolved in a solvent mixed with ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0178] Example 2
[0179] A positive electrode and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that a mixture of 70 wt% of a first positive electrode active material, 15 wt% of a second positive electrode active material, and 15 wt% of a third positive electrode active material was used as the positive electrode active material.
[0180] Comparative Example 1
[0181] A positive electrode and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the third positive electrode active material was not mixed, and a mixture of 70 wt% of the first positive electrode active material and 30 wt% of the second positive electrode active material was used as the positive electrode active material.
[0182] To aid understanding, the design details of the positive electrode active materials of the examples and comparative examples are briefly shown in Table 1 below.
[0183] First positive active material Second positive active material Third positive electrode active material 4.45V Lifespan (%, @50 cycles) Average voltage (V) Al coating (mol%) Zr coating (mol%) weight% Al doping (molar%) Al coating (mol%) Y Coating (Moll%) weight% Al doping (molar%) Mg doping (molar%) Al coating (mol%) weight% Example 1 1.0 (Wet) 0.2 70 2.0 0.4 0.1 20 0.5 0.5 0.1 10 98.3 3.83 Example 2 1.0 (Wet) 0.2 70 2.0 0.4 0.1 15 0.5 0.5 0.1 15 98.5 3.85 Comparative Example 1 1.0 (Wet) 0.2 70 2.0 0.4 0.1 30 - - - 0 97.3 3.80 Comparative Example 2 1.0 (Wet) 0.2 70 - - - 0 0.5 0.5 0.1 30 99.0 3.87
[0184] Evaluation Example 1
[0185] The lithium secondary batteries prepared in the examples and comparative examples were charged at 25°C with a constant current of 0.2C to an upper voltage limit of 4.45V and with a constant voltage of 0.05C, and then discharged at 0.2C to a cutoff voltage of 3.0V to perform initial charge and discharge. Subsequently, at 45°C, a cycle of charging at 1.0C and discharging at 1.0C in a voltage range of 3.0V to 4.45V was repeated 50 times or more, and the ratio of the 50-cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1 above.
[0186] In addition, the average voltage at 50% State of Charge (SOC) during initial discharge was measured and is shown in Table 1.
[0187] In addition, the density of the anode composite in the rolled state of the examples and comparative examples is shown in Table 1.
[0188] Referring to Table 1, it can be seen that compared to the comparative examples, the examples have a higher composite density of the anode, a higher average voltage, and superior lifespan characteristics when driven at a high voltage of 4.45V.
[0189] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims are also included within the scope of the present invention. Explanation of the symbols
[0190] 100: Lithium secondary battery 10: Positive electrode 20: Cathode 30: Separator 40: Electrode assembly 50: Case
Claims
Claim 1 A positive electrode active material comprising: a first positive electrode active material in the form of secondary particles formed by the aggregation of a plurality of primary particles, containing a lithium nickel-manganese composite oxide having a nickel content of 60 mol% or more relative to 100 mol% of the total metal excluding lithium; a second positive electrode active material in the form of a single particle, containing a lithium nickel-manganese composite oxide having a nickel content of 60 mol% or more relative to 100 mol% of the total metal excluding lithium; and a third positive electrode active material in the form of particles containing a lithium manganese oxide with a spinel structure represented by Chemical Formula 3: [Chemical Formula 3]Li a3 Mn x3 M 3 y3 O 4-b3 X b3 In Chemical Formula 3, 0.9≤a3≤1.8, 1.7≤x3≤2, 0≤y3≤0.3, 1.9≤x3+y3≤2.1, and 0≤b3≤0.1, and M 3 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S. Claim 2 In claim 1, the average particle size (D) of the secondary particles of the first positive active material. 50 ) is 10 μm to 20 μm, and the average particle size (D) of the single particles of the second positive active material is 50 ) is 0.5 μm to 8 μm, and the average particle size (D) of the particles of the third positive active material. 50 ) is a positive active material having a size of 5 μm to 12 μm. Claim 3 A positive active material according to claim 1, wherein, with respect to the total sum of the first positive active material, the second positive active material, and the third positive active material at 100 weight%, the first positive active material is included at 60 weight% to 90 weight%, the second positive active material is included at 5 weight% to 35 weight%, and the third positive active material is included at 5 weight% to 35 weight%. Claim 4 A positive active material according to claim 1, wherein, with respect to the total sum of the first positive active material, the second positive active material, and the third positive active material at 100 weight%, the first positive active material is included at 60 weight% to 85 weight%, the second positive active material is included at 10 weight% to 25 weight%, and the third positive active material is included at 5 weight% to 20 weight%. Claim 5 A positive electrode active material according to claim 1, wherein the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are identical or different, and each independently has a nickel content of 60 mol% to 80 mol% relative to 100 mol% of the total metal excluding lithium. Claim 6 In claim 1, the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently lithium nickel-manganese-aluminum composite oxides that further include aluminum in addition to nickel and manganese, and the positive electrode active material wherein the aluminum content in the lithium nickel-manganese-aluminum composite oxide is 1 mol% to 3 mol% with respect to 100 mol% of the total metal excluding lithium. Claim 7 In claim 1, the lithium nickel-manganese composite oxide of the first positive active material, the lithium nickel-manganese composite oxide of the second positive active material, and the lithium manganese oxide of the third positive active material are each independently positive active materials having a cobalt content of 0 mol% to 0.01 mol% relative to 100 mol% of the total metal excluding lithium. Claim 8 In claim 1, the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently positive electrode active materials represented by the following Chemical Formula 1: [Chemical Formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1 and M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S. Claim 9 A positive active material according to claim 8, satisfying 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.29 in the above chemical formula 1. Claim 10 In claim 1, the first positive active material further comprises a coating layer containing aluminum located on the surface of the secondary particle. Claim 11 A positive electrode active material according to claim 10, wherein the aluminum content of the coating layer is 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the first positive electrode active material. Claim 12 In claim 10, the coating layer is a positive active material further comprising zirconium, yttrium, or a combination thereof. Claim 13 In claim 12, the coating layer further comprises 0.05 mol% to 1 mol% of zirconium with respect to 100 mol% of metal excluding lithium in the first positive active material, and / or further comprises 0.05 mol% to 1 mol% of yttrium. Claim 14 In claim 10, the coating layer of the first positive active material is a positive active material in the form of a shell that continuously surrounds the surface of the secondary particle. Claim 15 In claim 10, the thickness of the coating layer of the first positive active material is 30 nm to 500 nm. Claim 16 In claim 10, the first positive active material further comprises a grain boundary coating portion containing aluminum located on the surface of the primary particles inside the secondary particles. Claim 17 In claim 1, the second positive active material is a positive active material further comprising a coating layer containing aluminum located on the surface of the single particle. Claim 18 A positive electrode active material according to claim 17, wherein the aluminum content of the coating layer is 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the second positive electrode active material. Claim 19 In claim 17, the coating layer of the second positive active material is a positive active material in the form of a shell that continuously surrounds the surface of the single particle. Claim 20 In claim 17, the thickness of the coating layer of the second positive active material is 30 nm to 500 nm. Claim 21 In paragraph 17, the coating layer of the second positive active material is a positive active material further containing yttrium. Claim 22 A positive electrode active material according to claim 21, wherein the yttrium content of the coating layer is 0.1 mol% to 1 mol% with respect to 100 mol% of the total metal excluding lithium in the second positive electrode active material. Claim 23 In claim 21, the positive active material wherein aluminum exists in the form of a continuous film and yttrium exists in the form of an island in the coating layer of the second positive active material. Claim 24 In claim 21, the second positive active material comprises a first coating layer located on the surface of the single particle and containing aluminum, and a second coating layer located on the first coating layer and containing yttrium. Claim 25 In claim 1, the third positive active material is a positive active material in the form of secondary particles formed by the aggregation of a plurality of primary particles. Claim 26 In claim 1, the lithium manganese-based oxide of the third positive electrode active material is a positive electrode active material that further comprises aluminum, magnesium, yttrium, or a combination thereof in addition to manganese. Claim 27 A positive active material according to claim 1, wherein in chemical formula 3, 1.8≤x3≤2, and 0≤y3≤0.
2. Claim 28 In claim 27, the lithium manganese-based oxide of the third positive electrode active material is a positive electrode active material represented by the following chemical formula 4: [Chemical Formula 4]Li a4 Mn x4 Al y4 Mg z4 M 4 w4 O 4-b4 X b4 In Chemical Formula 4, 0.9≤a4≤1.8, 1.7≤x4<2.0, 0 <y4≤0.015, 0<z4≤0.010, 0≤w4<0.3, 1.9≤x4+y4+z4+w4≤2.1, 및 0≤b4≤0.1이고 M 4 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S. Claim 29 In claim 1, the third positive active material is a positive active material further comprising a coating layer containing aluminum located on the surface of the particle. Claim 30 In claim 29, the anode active material comprising 0.01 mol% to 1 mol% of aluminum in the coating layer relative to 100 mol% of metal excluding lithium in the third anode active material. Claim 31 An anode comprising an anode current collector and an anode active material layer located on the anode current collector, wherein the anode active material layer comprises an anode active material according to any one of claims 1 to 30. Claim 32 In claim 31, the anode having a density of the anode active material layer of 3.5 g / cc to 3.7 g / cc. Claim 33 A lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte according to paragraph 31. Claim 34 In paragraph 33, a lithium secondary battery having a charging voltage of 4.3 V to 4.6 V.
Citation Information
Patent Citations
Positive active material, and positive electrode and lithium battery containing the material
KR1020110109879A
Positive electrode active material for lithium secondary battery, preparing method of the same, positive electrode and lithium secondary battery including the same
KR1020190117199A
Lithium secondary battery and method of manufacturing the same
KR1020230009522A
Positive active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same
KR1020230095271A
